Design of L-S band broadband power amplifier using microstip lines - Mohamed Ribate; Rachid Mandry; Jamal Zbitou; Larbi El Abdellaoui; Ahmed Errkik; Mohamed Latrach; Ahmed Lakhssassi (International Journal of Electrical and Computer Engineering (IJECE), 2020)
This contribution introduces a novel broadband power amplifier design, operating in the frequency band ranging from 1.5 GHz to 3 GHz which cover the mainstream applications running in L and S bands. Both matching and biasing networks are synthesized by using microstrip transmission lines. In order to provide a wide bandwidth, two broadband matching techniques are deployed for this purpose, the first technique is an approximate transformation of a previously designed lumped elements matching networks into microstrip matching circuits, and the second technique is a binomial multi-sections quarter wave impedance transformer. The proposed work is based on ATF-13786 active device. The simulation results depict a maximum power gain of 16.40 dB with an excellent input and output matching across 1.5 GHz ~ 3 GHz. At 2.2 GHz, the introduced BPA achieves a saturated output power of 16.26 dBm with a PAE of 21.74%, and a 1-dB compression point of 4.5 dBm input power level. The whole circuitry is unconditionally stable over the overall bandwidth. By considering the broadband matching, the proposed design compares positively with the most recently published BPA.